Chemotaxonomic contribution to the Sideritis species dilemma on the Balkans. (August 2015) - Stanoeva, Jasmina Petreska; Stefova, Marina; Stefkov, Gjose; Kulevanova, Svetlana; Alipieva, Kalina; Bankova, Vassya; Aneva, Ina; Evstatieva, Ljuba N.
Abstract: Forty-two samples of Sideritis species ( Sideritis scardica, Sideritis raeseri, Sideritis syriaca, Sideritis taurica and Sideritis lanata ) from the Balkan Peninsula were evaluated for their polyphenolic profiles in order to establish a correlation between the taxonomy, geographical location and nature and content of phenolic compounds. Eight compounds were detected in all analyzed Sideritis samples: 5-caffeoylquinic acid, lavandulifolioside, verbascoside, isoscutellarein 7- O -allosyl(1→2)glucoside, hypolaetin 7- O -[6‴- O -acetyl]-allosyl(1→2)glucoside, isoscutellarein 7- O -[6‴- O -acetyl]-allosyl(1→2)glucoside, 3′- O -methylhypolaetin 7- O -[6‴- O -acetyl]-allosyl(1→2)glucoside and 4′- O -methylhypolaetin 7-O-[6‴- O -acetyl]-allosyl-(1→2)-[6″- O -acetyl]-glucoside). They present from 50 to 80% of total phenolic content in S. scardica, S. raeseri, S. syriaca and S. taurica and up to 90% in S. lanata and the similarity of their polyphenolic profiles implies that they are systematically very closely related. Based on their polyphenolic patterns, very good differentiation between the samples of S. lanata (sect. Hesiodia ) and S. scardica, S. syriaca and S . raeseri (sect. Empedoclia ) was observed, that is mainly due to the very high content of 5-cafeoylquinic acid and very low amount of phenylethanoid glycosides and flavonoid glycosides. The obtained results demonstrate considerable degree of similarity between S. scardica, S. raeseri and Bulgarian S. syriaca that give contribution to the dilemma that Bulgarian S. syriaca is very similar to Turkish S. taurica and suggest further verification of its taxonomic status. Graphical abstract: Highlights: Polyphenolic patterns of 42 Balkan Sideritis samples (4 species) were determined. Correlation of polyphenolic profile to taxonomy was evaluated by PCA. Differences in polyphenols found to be more related to location than to species. Results suggest that Bulgarian Sideritis syriaca is closer to Turkish Sideritis taurica .